Implementation Of The Stad Learning Model In Improving Student Learning Outcomes In Pai Subjects At Sman 2 Tambun Utara - Acep Mulyadi; Abim Triatna; Ahmad Faiz; Muhammad Nur Ikhsan; Robiatul Adawiyah; Syarifah Salsa Nur Fadhilah (Lumbung Pare Cendekia, 2024)
This study is oriented to the saturation of students in the following subjects PAI. Many students are not focused and tend to get bored during the lesson. Teacher-centered learning methods will eliminate the stimulus of learners to the lesson. The purpose of this study was to examine the efficiency in the implementation of the STAD (Student Teams Achievement Division) method in order to increase the academic achievement of students at the secondary school level. The research aimed to focus on measuring the evaluation of academic achievement progress, interaction between students in groups, and understanding of concepts in learning materials. The approach in this study uses a descriptive quantitative approach. Implementation activities begin with planning, implementation, observation and reflection. The results showed that there was an increase in significance by using the STAD type. Pre PTK, sirklus 1, sirklus 2, sirklus 3 with the acquisition of the first cycle score, which is Nine students (25.70%) were able to meet the minimal required value, with an average score of 69.8. Moreover, in Cycle 2, twenty-five students (71%) obtained an average score of 79.71, which was the minimum criterion. Nevertheless, the pupils have not met the success indicator of 85, thus the researcher moves on to cycle stage 3. The number of students that met the minimal standard score in this cycle grew to 35, or 100%, with an average score of 91.11